Impact of early intervention on outcome following mild head injury in adults. Issue 3 (1st September 2002) - Ponsford, J; Willmott, C; Rothwell, A; Cameron, P; Kelly, A-M; Nelms, R; Curran, C
Abstract : Background: The impact of mild head injury is variable and determinants of outcome remain poorly understood. Results of previous intervention studies have been mixed. Objectives: To evaluate the impact on outcome of the provision of information, measured in terms of reported symptoms, cognitive performance, and psychological adjustment three months postinjury. Methods: 202 adults with mild head injury were studied: 79 were assigned to an intervention group and were assessed one week and three months after injury; 123 were assigned to a non-intervention control group and were seen at three months only. Participants completed measures of preinjury psychological adjustment, concurrent life stresses, post-concussion symptoms, and tests of attention, speed of information processing, and memory. Subjects seen at one week were given an information booklet outlining the symptoms associated with mild head injury and suggested coping strategies. Those seen only at three months after injury did not receive this booklet. Results: Patients in the intervention group who were seen at one week and given the information booklet reported fewer symptoms overall and were significantly less stressed at three months after the injury. Conclusions: The provision of an information booklet reduces anxiety and reporting of ongoing problems.